cross multiply
I am assuming you mean (N+3) / (N+1) = 3/2
multiply both sides by 2
2(N+3) / (N+1) = 3
multiply both sides by (N+1)
2(N+3) = 3(N+1)
expand the brackets
2N + 6 = 3N + 3
Solve for N
If you actually mean
N + (3/N) + 1 = 3/2
This is a little more advanced. You would need to have
N^2 + 3 + N = 3N/2 {multiply both sides by N}
N^2 + N - 3N/2 + 3 = 0
N^2 - N/2 + 3 = 0
Use quadratic equation to find the roots
N = ((1/2) +/- SQRT(1/4 - 4.1.3)) / 2
giving you 2 imaginary roots
N = 1/4 +/- SQRT(11&3/4)/2
very messy :(
2007-05-21 13:16:22
·
answer #1
·
answered by Orinoco 7
·
0⤊
0⤋
Assume question reads as:-
(n + 3) / (n + 1) = 3 / 2
2n + 6 = 3n + 3
n = 3
2007-05-21 23:36:27
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
N+3/N+1=3/2
N(N+3/N+1)=N(3/2)
N^2+3+N=3/2N ; N is not 0
N^2-N/2+3=0
2N^2-N+6=0
N= [ -(-1)+ - sqrt( (-1)^2-4*2*6 ) ] /2*2 = [ 1+ - sqrt(-47) ] /4 = no answer
2007-05-21 13:32:56
·
answer #3
·
answered by sothanaphan 2
·
0⤊
0⤋
2n^2+6+2n=3n
2n^2-1n+6=0
...
reffering the question, the task is not :
(n+3)/N .... but actually n+3/n ....that in mathematics means : n+ (3/n) ...
If he discriminant ( sqrt(-47)) is <0,
the result of the above should be two complex numbers ...
(1+sqrt(-47))/4 and
(1-sqrt(-47))/4
2007-05-21 13:17:55
·
answer #4
·
answered by osmantus 2
·
0⤊
0⤋
2(N+3)=3(N+1) (Cross multiply)
2N+6=3N+3
3=N (Combining like terms on the same side)
2007-05-21 13:20:13
·
answer #5
·
answered by Chaotic_Shadow 3
·
0⤊
0⤋
mutliply both sides by (n+1)
so it becomes n+3 = 3/2(n+1)
then n+3 = 3/2n + 3/2
then subtract n from both sides and subtract 3/2 from both sides
1/2n = 1.5
n =3
2007-05-21 13:17:04
·
answer #6
·
answered by shinko58 1
·
0⤊
0⤋
very simple. cross mutiply it
2x (n+3) = 3x (n+1)
2n+ 6= 3n + 3
2n-3n = -6+3
-n=-3
n=3
thats the answer
2007-05-21 13:17:58
·
answer #7
·
answered by jos3308 2
·
0⤊
0⤋
once you have an prolonged question, you may enter it in the top-rated factors area. in any different case, it could desire to get cut back off like it replaced into right here. EDIT: shop putting areas until all of it exhibits up wisely in the preview. initiate via putting areas around - and + indications. Yahoo solutions is stupid that way...
2016-11-25 23:25:30
·
answer #8
·
answered by cruickshank 4
·
0⤊
0⤋
n+3/n+1=3/2
lcd=2(n+1)
2(n+3)=3(n+1)
2n+6=3n+3
2n-2n+6=3n-2n+3
6=n+3
3=n
2007-05-21 13:24:54
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
Wrong question.
2007-05-21 13:25:34
·
answer #10
·
answered by Mark 6
·
0⤊
0⤋